2018
DOI: 10.31234/osf.io/depw9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remembering “primed” words: A counter-intuitive effect of repetition on recognition memory

Abstract: The present study examines the effect of immediate repetition on recognition memory. In a series of 4 experiments, the study phase task was to name aloud a word that was immediately preceded by either the same word (repeated trials) or a different word (not-repeated trials). Across experiments, performance in the study phase demonstrated the anticipated benefit in naming times for repeated trials. More important, performance in the test phase revealed greater sensitivity for not-repeated than repeated trials. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(29 citation statements)
references
References 9 publications
7
21
0
1
Order By: Relevance
“…Indeed, there were null effects of repetition on recognition performance in the vowel count and name groups, and greater sensitivity for repeated than for not-repeated targets in the semantic group. These results demonstrate the counter-intuitive finding reported by Rosner et al (2017) does not always occur with the repetition method used here. Specifically, when primes are encoded in such a way that participants are likely to remember them at test (according to the levels of processing principle), recognition performance is better for repeated than for not-repeated targets.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Indeed, there were null effects of repetition on recognition performance in the vowel count and name groups, and greater sensitivity for repeated than for not-repeated targets in the semantic group. These results demonstrate the counter-intuitive finding reported by Rosner et al (2017) does not always occur with the repetition method used here. Specifically, when primes are encoded in such a way that participants are likely to remember them at test (according to the levels of processing principle), recognition performance is better for repeated than for not-repeated targets.…”
Section: Discussionsupporting
confidence: 81%
“…First, as reported by Rosner et al (2017), and as observed in Experiment 1, recognition was better for not-repeated than repeated targets when participants ignored the primes in the study phase. Although this result only approached significance in the present experiment, the reliability of this effect across six similar variants of this procedure (Rosner et al, 2017; Experiment 1 of the present study) offers plenty of supporting evidence that there is a real and replicable difference in recognition memory between not-repeated and repeated target conditions. Second, recognition was just slightly better for repeated than not-repeated targets when participants read the primes in the study phase.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations